2013
DOI: 10.1111/nph.12541
|View full text |Cite
|
Sign up to set email alerts
|

Bark functional ecology: evidence for tradeoffs, functional coordination, and environment producing bark diversity

Abstract: SummaryThe causes underlying bark diversity are unclear. Variation has been frequently attributed to environmental differences across sites. However, variation may also result from tradeoffs and coordination between bark's multiple functions. Bark traits may also covary with wood and leaf traits as part of major dimensions of plant variation.To assess hypotheses regarding tradeoffs and functional coordination, we measured bark traits reflecting protection, storage, mechanics, and photosynthesis in branches of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
168
4
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(200 citation statements)
references
References 72 publications
19
168
4
5
Order By: Relevance
“…1). One explanation can be related to leaf phenology of trees in central Amazonia, since production of leaves and bark water content seem to be interrelated (Clark & Gibbs 1957, Rossel et al 2014. In central Amazonia the production of litter tends to increase in the dry season (Luizão & Schubart 1987), which suggests that the production of new leaves can follow a similar pattern (Doughty & Goulden 2008).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
See 1 more Smart Citation
“…1). One explanation can be related to leaf phenology of trees in central Amazonia, since production of leaves and bark water content seem to be interrelated (Clark & Gibbs 1957, Rossel et al 2014. In central Amazonia the production of litter tends to increase in the dry season (Luizão & Schubart 1987), which suggests that the production of new leaves can follow a similar pattern (Doughty & Goulden 2008).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…In Amazonian trees, Nogueira et al (2008) reported wood water content in the range of 22 to 67% (mean of 33.9%), with moisture increasing toward the tip of the tree. Variations in water content of wood and bark have been attributed to environmental and phylogenetic factors, with higher water contents often associated with thicker barks (Rossel et al 2014). In temperate and tropical forests, tree water content of poles and branches can vary seasonally (Gibbs 1958, Chapotin et al 2006).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…The moisture content in the leaves is higher and more stable than in the tree bark. This is because in the tree bark, the water and solutes may buffer the daily or seasonal fluctuations in water availability in the tree tissues (Rosell et al 2014).…”
Section: Proximate Chemical Analysismentioning
confidence: 99%
“…Considerando-se que uma das funções da casca é o armazenamento de água (ROSELL et al, 2014), os valores negativos observados da taxa de incremento podem ser atribuídos ao uso dessa reserva hídrica pela planta durante o período mais desfavorável. Adicionalmente, a variação da umidade relativa do ar leva a oscilação da largura da casca, já que ela está em contato direto com o ambiente (ZWEIFEL et al, 2000;STAHL et al, 2010).…”
Section: Gs* Imc (Mm) Iac (Mm)unclassified